Peripheral venipuncture in hospitalized people: GIBI technique supporting the procedural approach to social representations (Research, Society and Development, 2021)
The objective was to discuss the social representations of peripheral venipuncture, the self-perception of its stages, manifestations of vascular trauma and post-catheter removal procedures according to hospitalized adults. The design adopted was qualitative according to the procedural approach of Social Representations. Research carried out in a private hospital in which people admitted to the clinical-surgical sectors with veins punctured for therapeutic purposes, aged ≥18 years, participated. Data collected: characterization, profile of experiences with the puncture, individual interview in depth recorded and technique of cutting and pasting comic books based on guiding questions. Data processed in SPSS version 26 and NVivo Pro11® software. 148 people participated who identified bleeding, pain and ecchymosis as manifestations of vascular trauma; use of adhesive tape as a covering and they did not use local compresses. The selected figures approached the representational contents and portrayed self-perceptions/expectations about the puncture. It is concluded that the puncture was tolerated by users as part of the therapy and is linked to expectations of improvement.